Pastillation: A novel technology for development of oral lipid based multiparticulate controlled release formulation - Shukla D.; Chakraborty S.; Singh S.; Mishra B. (My University, 2025)
A novel technique, 'Pastillation' to fabricate lipid based oral multiparticulate controlled release dosage forms for first time in pharmaceutical field is reported. An in-house laboratory scale device was designed to generate pastilles of doxofylline loaded stearic acid. Pastilles formed were characterized for drug content uniformity, drug release profile, morphology and contact-angle. The optimized conditions for pastillation were 1.00. cm dropping height, 20. G needle orifice and 4°C plate temperature which produced good pastilles of uniform size (2.5-3.0. mm) with contact angle above 90°. This multiparticulate system has very good flow property and is very uniform in size, weight and drug content and is able to sustain the drug release for a period of 24. h. This is a very simple method for producing lipid-based multi-particulate system as compared to other available techniques (melt-extrusion and freeze-pelletization) which can further be filled in capsules/sachets. The biggest advantage of this technology is that the large-scale equipment for pastillation is well-established in chemical industries. Therefore, use of this unique dosage form may open new avenue in the field of drug delivery which may even be an alternative for line extension or preparing patent non-infringing products of existing formulations. © 2011 Elsevier B.V.